2021
DOI: 10.3332/ecancer.2021.1167
|View full text |Cite
|
Sign up to set email alerts
|

Role of sentinel lymph node biopsy for cutaneous melanoma in elderly patients: preliminary results in a Latin-American population

Abstract: Introduction:In melanoma, lymph node status constitutes the most important prognostic factor among patients with locoregional disease. It has been postulated that elderly patients present less metastatic involvement in sentinel lymph node (SLN). Our objective was to analyse the results and evolution of patients ≥ 70 years-old with cutaneous melanoma in whom sentinel lymph node biopsy (SLNB) was carried out.Methods: Retrospective analysis of 194 patients with primary CM who had a SLNB between 2005 and 2020 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…31 SLNB success and positivity rates were reported by all the papers, however, only two studies had a suitable control for comparisons to a younger population. 28,30 Histology reports were provided by two of the papers, who also documented a higher Breslow thickness in their elderly groups similar to our results. 8,17 Only one study reported on the incidence of seroma, 31 with no papers providing a thorough complication profile for SLNB in the older population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…31 SLNB success and positivity rates were reported by all the papers, however, only two studies had a suitable control for comparisons to a younger population. 28,30 Histology reports were provided by two of the papers, who also documented a higher Breslow thickness in their elderly groups similar to our results. 8,17 Only one study reported on the incidence of seroma, 31 with no papers providing a thorough complication profile for SLNB in the older population.…”
Section: Discussionsupporting
confidence: 88%
“…All but one study was retrospective in nature 31 . SLNB success and positivity rates were reported by all the papers, however, only two studies had a suitable control for comparisons to a younger population 28,30 . Histology reports were provided by two of the papers, who also documented a higher Breslow thickness in their elderly groups similar to our results 8,17 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Age has been discussed by many authors, with the study results implying that being young increases both the SLNB positivity rates as well as the survival rates, whereas elderly patients are less likely to be SLNB-positive, but have a worse prognosis [32,33]. Other single-center studies report higher SLNB positivity rates in senior patients as well as higher SLNB surgical complication rates, while some authors express the benefits of SLNB in senior population with regard to staging and exploring the possibilities of adjuvant therapy [3,34]. Thus, certain clinical scenarios could still be considered a grey area in SLNB decision making.…”
Section: Discussionmentioning
confidence: 99%